2016
DOI: 10.1002/jmri.25146
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fat on liver T1 measurements using modified Look–Locker inversion recovery (MOLLI) methods at 3T

Abstract: PurposeTo characterize the effect of fat on modified Look–Locker inversion recovery (MOLLI) T 1 maps of the liver. The balanced steady‐state free precession (bSSFP) sequence causes water and fat signals to have opposite phase when repetition time (TR) = 2.3 msec at 3T. In voxels that contain both fat and water, the MOLLI T 1 measurement is influenced by the choice of TR.Materials and MethodsMOLLI T 1 measurements of the liver were simulated using the Bloch equations while varying the hepatic lipid content (HLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 35 publications
9
70
0
Order By: Relevance
“…Here, SE-EPI T 1 data were acquired with fat suppression, removing the effect of fat on the calculated liver T 1 value, which results from the water liver tissue compartment. In contrast, T 1 ∗ data acquired with a bFFE readout is affected by the hepatic fat content in a manner dependent on the phase between the fat and water signal (as determined by field strength and repetition time) [28]. Further since our T 1 measurement method is both respiratory triggered and multi-slice, it allows a large volume of the liver to be sampled [mean (± SD) of 3911 (± 1463) voxels covering 281 (± 106) cm 3 ] in a reasonable imaging time without the need for breath-hold, making this imaging scheme ideal for patient studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, SE-EPI T 1 data were acquired with fat suppression, removing the effect of fat on the calculated liver T 1 value, which results from the water liver tissue compartment. In contrast, T 1 ∗ data acquired with a bFFE readout is affected by the hepatic fat content in a manner dependent on the phase between the fat and water signal (as determined by field strength and repetition time) [28]. Further since our T 1 measurement method is both respiratory triggered and multi-slice, it allows a large volume of the liver to be sampled [mean (± SD) of 3911 (± 1463) voxels covering 281 (± 106) cm 3 ] in a reasonable imaging time without the need for breath-hold, making this imaging scheme ideal for patient studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using a modified look-locker inversion recovery (MOLLI) T 1 mapping method with bFFE readout have shown a correlation with fibrosis [22]. However, this technique requires a breath-hold for each slice acquired, and it has been shown that hepatic fat content can be large enough to cause severe MOLLI T 1 alterations [28]. The distribution of liver T 1 values (Gaussian FWHM) was also shown to increase with the worsening portal hypertension, reflecting the increasing heterogeneity of T 1 values across the liver volume.…”
Section: Discussionmentioning
confidence: 99%
“…The signal produced by bSSFP is dependent on the T 1 and T 2 of imaged proton species, flip angle and off‐resonance frequency . The frequency dependence, in particular, can result in complex behaviour of the bSSFP signal during T 1 recovery when the imaged voxels contain both fat and water . With typical imaging parameters and clinically relevant fat fraction, this leads to an overestimation of the liver water MOLLI T 1 , at odds with the decrease expected in a simple partial volume model.…”
Section: Introductionmentioning
confidence: 99%
“…This counterintuitive increase in MOLLI T 1 with fat is in addition to the effect of iron deposits that reduce T 1 and T 2 . Magnetization transfer, heart rate, repetition time of the bSSFP readout and B 0 inhomogeneity also influence MOLLI T 1 values.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches aim to correct T 1 by quantifying hepatic lipid content using localised cardiac-triggered proton spectroscopy in a selected region of interest [12] . However, this approach leaves T 1 vulnerable to hepatic fat interference [21] .…”
Section: T 1 Measurements Of Fibrosismentioning
confidence: 99%